LONG-TERM CHANGE OF WATER QUALITY IN THE RESERVOIR OF THE ISAHAYA BAY RECLAMATION PROJECT - Y. Mitsugi; N. Vongthanasunthorn; Y. Mishima; K. Koga; H. Araki; P. Ittisukananth (International Association of Lowland Technology, 2013)
In 1997, the Isahaya Reservoir was constructed at the innermost part of Isahaya Bay, Japan to prevent natural disasters and to develop water resources for large-scale farm lands. The main purposes of this study were to analyze the mechanisms underlying the water quality changes observed and to collect significant information for water quality management at the reservoir. Observed water quality parameters on chlorophyll-a, suspended solids, total nitrogen, dissolved inorganic nitrogen, total phosporus, dissolved inorganic phosphorus and chloride ion were analyzed by using a water quality model. It was found taht the results obtained from the developed water quality model agreed with the observed data. After calibrating the observed data, a simple sensitivity analysis was conducted to demonstrate the mechanisms of the water quality changes. The major water quality problems were suspended solids that had been resuspended by strong wind and eutrophication due to the enrichment of nutrients. The major mechanisms of water quality changes in the Isahaya reservoir were a coagulation and flocculation by brackish water and the transformation process of phosphorus. The coagulation affected the settling velocity of suspended solids and dissolved phosphorus. It was also revealed that the resolution process of dissolved phosphorus from suspended solids was controlled by the salinity.